Role of reactive thrombocytosis after primary cytoreductive surgery in advanced ovarian cancer - Kim, Myeong-Seon; Baek, Seung Hun; Noh, Joseph J.; Shim, Jung In; Kang, Jun Hyeok; Jeong, Soo Young; Choi, Chel Hun; Kim, Tae-Joong; Lee, Jeong-Won; Lee, Yoo-Young (Frontiers in Oncology, 2022)
We investigated the incidence of reactive thrombocytosis after maximal cytoreductive surgery in advanced epithelial ovarian cancer (EOC) and its role in patient survival. We retrospectively reviewed electronic medical records of patients who underwent primary cytoreductive surgery for advanced EOC from January 1, 2012, and December 31, 2017. We analyzed the serum platelet counts at various time points from before surgery, during peri-operative period, and on each cycle of adjuvant chemotherapy. A total of 474 patients were eligible for the analysis. Among them, 401 patients (84.6%) had FIGO stage III disease status. The most common histology type was serous adenocarcinoma (405 patients, 85.4%). Seventy-nine patients (22.6%) received splenectomy and optimal cytoreduction was achieved in 326 patients (68.8%). A week after surgery, thrombocytosis was observed in 165 patients (34.8%) in the entire cohort. Higher platelet counts were observed in patients with splenectomy compared with patients without splenectomy. In particular, thrombocytosis on the 5th cycle of adjuvant chemotherapy showed most significant effects on overall survival in multivariate analysis. In a logistic regression model, splenectomy significantly attributed to thrombocytosis on the 5th cycle of chemotherapy. Reactive thrombocytosis after primary cytoreductive surgery was associated with poor survival in advanced EOC, particularly when thrombocytosis was observed during adjuvant chemotherapy.